Evolution of Corporate Leverage on the JSE from 1994 to 2016 - Mokoko, Tseko (Department of Finance and Tax, 2023)
In this paper, an attempt has been made to examine the evolution of corporate leverage of companies listed on the Johannesburg Stock Exchange (JSE) from 1994 to 2016. Analysis of the data set is organized around a sample of 126 listed companies across twelve sub-sector industries, namely, Banks, Financial Services, Life Insurance, Fixed Line Telecommunications, Nonlife Insurance, Health Care Equipment and Services, Pharmaceuticals and Biotechnology, Media, Technology Hardware and Equipment, Software and Computer Services, Electronic and Electrical Equipment and Support Services. 621 delisted companies were also briefly analysed to eliminate survivorship bias. Results of multiple regressions using two primary leverage measures and six commonly used determinants of capital structure were varied. Tangibility and growth were negatively related to debt while cost of debt was positively related to debt. Firm size, profitability and corporate tax rate yielded a varied relationship with corporate leverage. Only the growth capital structure determinant showed statistical significance. The overall findings indicate a rise in corporate leverage that coincides in tandem with major local and international economic events.